Analysis of the Addition e Node B in 4G LTE Network for Coverage Area - Ulfah, Maria (International Journal of Engineering and Technology, 2018)
As the number of LTE 4G network subscribers increases, telecom operators must expand their coverage area to be able to serve the telecommunications needs of customers. Research on 4G LTE is still interesting to be studied because 4G LTE network is still developed.This study discusses the effect of the addition of e Node B to the coverage area of 4G LTE network. The research method used is survey, simulation. This research is done by taking data of telecommunication operator in north Balikpapan. From the research results for the 4G LTE network need to add 4 e Node B from 14 to 18 e Node B. By addition of e Node B number increased coverage area of 4G LTE network from 89.108 km2 to 132 km2Â Â